2017
DOI: 10.1590/s1518-8787.2017051006655
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of leprosy in a hyperendemic State in North Brazil

Abstract: OBJECTIVE To identify the socioeconomic, demographic, operational, and health service-related factors associated with the occurrence of leprosy in a hyperendemic State in North Brazil.METHODS This is an ecological study based on secondary data from the Sistema de Informações de Agravos de Notificação in municipalities of the State of Tocantins from 2001 to 2012. Units of analysis were the 139 municipalities of the State. Negative binomial log linear regression models were used to estimate incidence rate ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0
19

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 28 publications
5
27
0
19
Order By: Relevance
“…The 2006 decrease followed the lower prevalence reported from other regions in Brazil and is likely a reflection of the removal of long-standing cases by the elimination initiative. 18,21,22 Despite the elimination initiative, leprosy transmission and incidence have continued in the community, and other factors, such as living conditions and socio-economic factors, are likely to play a role in facilitating its persistence.…”
Section: Discussionmentioning
confidence: 99%
“…The 2006 decrease followed the lower prevalence reported from other regions in Brazil and is likely a reflection of the removal of long-standing cases by the elimination initiative. 18,21,22 Despite the elimination initiative, leprosy transmission and incidence have continued in the community, and other factors, such as living conditions and socio-economic factors, are likely to play a role in facilitating its persistence.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the diagnosis of the disease with campaigns was associated with late diagnosis in the Tocantins territory, demonstrating the importance of carrying out this strategy to search for suppressed demands, especially in extensive areas, focusing on high-risk groups and socioeconomically disadvantaged populations 8,16 . Active search is an important tool to control leprosy in hyperendemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies described unequal patterns in the space-time trend of leprosy indicators for Tocantins, related to issues such as health service coverage, borders with hyperendemic states, migration, social vulnerability of the disease, and urbanization 3,[6][7][8]27 . One of these studies identified spatial patterns to detect cases in children under 15 years of age using local empirical Bayesian analysis, which classified more than 90% of the cities of Tocantins as hyperendemic 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outro aspecto relacionado a baixas condições socioeconômicas é o acesso a alimentação adequada, pois a baixa nutrição está relacionada ao risco aumentado para a hanseníase (PATIL, 2013;FEENSTRA et al, 2011). Monteiro et al (2017) fazem uma relação importante entre a incidência da hanseníase e a cobertura do Programa Bolsa Família (PBF), pois demonstram que a razão das taxas de incidência da doença foram superiores em municípios com menor percentual da população com cobertura pelo PBF pois, ao considerar a renda per capita de até meio salário por domicílio (condição mínima para o recebimento do benefício), apresentou um risco menor. Todavia tal resultado não foi observado no cenário de de Foz do Iguaçu pois os resultados demonstraram que conforme diminui a renda, o risco para hanseníase aumenta.…”
Section: Discussionunclassified